The Male Householder and the Hypermasculine Deity: Malayalam-Language Films Based on the Sabarimala Temple in Kerala - Sooraj S.S.; Krishna K.R.K.; Mishra A.K. (My University, 2025)
The Sabarimala Temple in the South Indian state of Kerala garnered national and global attention following violent protests against the Indian Supreme Court’s verdict in September 2018, allowing the entry of women of menstruating age to the temple. By studying popular Malayalam films released over the years, this article examines how beliefs around Sabarimala are intrinsically linked to the notion of the male householder, while simultaneously marginalizing women’s religiosity. We first delineate the influence of the film Swami Ayyappan (1975) in establishing the role of the deity Ayyappa in the welfare of hetero-patriarchal families in Kerala. The second section studies how the film Chinthavishtayaya Shyamala (1998) problematizes the centrality of the male householder in Kerala after liberalization and the way that the Sabarimala pilgrimage is used within the narrative to reinstate the patriarchal male. The following section examines the film The Great Indian Kitchen (2021) against the backdrop of the Sabarimala protests and developments in gender regimes in Kerala post-2000. Poised at the intersections of gender and religion, we argue that this film unravels the subtle forms of everyday gender discrimination and the undesirability of patriarchal masculinity in contemporary Kerala. It concludes by discussing briefly a few other recent Malayalam films, like Malikappuram (2022), released after the women’s temple-entry protests, to show their treatment of the Sabarimala issue and the politics of gender therein. © 2023 Taylor & Francis Group, LLC.